P129 Designing sexual health services to meet the needs of young people in the uk: results from a qualitative study to inform discrete choice experiment (DCE) development. (8th June 2017) - Jackson, Louise; Ross, Jonathan; Al-Janabi, Hareth; Roberts, Tracy
Abstract : Introduction: Young people experience the greatest burden of sexually transmitted infections (STIs) in the UK. STI screening is now being provided in a wider range of settings such as GP surgeries, pharmacies, and via online services. It is important that screening provision reflects the preferences of young people from different cultural backgrounds. The specific aims of the study were: to explore the factors that are important to young people when thinking about and participating in STI screening in different settings; to examine the characteristics of screening services that influence choices about screening. Methods: Qualitative methods were used to inform the development of a discrete choice experiment (DCE) to provide quantitative measurement and analysis of the choices made by young people in relation to STIs. A series of eight focus groups and 2 interviews were undertaken with 43 young people in specialist and community settings, with the inclusion of participants from different cultural groups. Discussions were transcribed and analysed using constant comparison methods. Results: The focus groups revealed a range of aspects of screening that were important to young people. The main themes identified related to stigma, understanding of STIs and risk, setting, interactions with staff, convenience and the nature of the screening test. Attributes for the DCE were developed around waiting times, setting, type of screening test, and staff attitude. Discussion: The complexities and challenges involved in designing and delivering services for young people are highlighted, particularly in relation to reflecting the preferences of young people from varied cultural backgrounds.